2020
DOI: 10.1007/s11356-020-10551-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climatological parameters on the outbreak spread of COVID-19 in highly affected regions of Spain

Abstract: The coronavirus (COVID-19) pandemic is infecting the human population, killing people, and destroying livelihoods. This research sought to explore the associations of daily average temperature (AT) and air quality (PM 2.5) with the daily new cases of COVID-19 in the top four regions of Spain (Castilla y Leon, Castilla-La Mancha, Catalonia, and Madrid). To this end, the authors employ Pearson correlation, Spearman correlation, and robust panel regressions to quantify the overall co-movement between temperature,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…Alternatively, the findings conclude that air pressure, humidity, and temperature significantly affect the cases in Peru. Air pressure, PM2.5, and temperature have a statistically significant impact (at 1% level of significance) on the rising cases in Russia and Spain (contradicting the result by Briz-Redón and Serrano-Aroca ( 2020 ) and Shahzad et al ( 2020 ) which prove no relation between temperature and Covid-19 cases in Spain). The UK exhibits a statistically significant impact by humidity, temperature, and wind speed on its confirmed cases.…”
Section: Findings and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Alternatively, the findings conclude that air pressure, humidity, and temperature significantly affect the cases in Peru. Air pressure, PM2.5, and temperature have a statistically significant impact (at 1% level of significance) on the rising cases in Russia and Spain (contradicting the result by Briz-Redón and Serrano-Aroca ( 2020 ) and Shahzad et al ( 2020 ) which prove no relation between temperature and Covid-19 cases in Spain). The UK exhibits a statistically significant impact by humidity, temperature, and wind speed on its confirmed cases.…”
Section: Findings and Discussionmentioning
confidence: 67%
“…The developing countries categorized by the slow growth rate, poor healthcare infrastructure, and large population (a majority of them living in extreme poverty) have been severely affected by the Covid-19 pandemic (Sharma et al 2020b , c ). The Covid-19 pandemic resulted in a substantial loss of human capital of the economy (Shahzad et al 2020 ). It thus increased the total (public and private) expenditure on healthcare (Lee and McKibbin 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cone of influence separates the significant region from the rest with a thick black lining drawn from top to bottom on both sides. 14,36,37 Results and Discussion Argentina, and Colombia have been the most affected countries by the COVID-19 outbreak, where lack of health facilities and state response have contributed to the most infections in these countries. We utilized the Kendall correlation coefficient to examine the correlation association between variables included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Cone of influence separates the significant region from the rest with a thick black lining drawn from top to bottom on both sides. 14 , 36 , 37 …”
Section: Methodsmentioning
confidence: 99%
“…Shahzad et al studied the impact of daily temperature and PM2.5 air particles on COVID-19 widespread in Spain. The result showed a direct impact on air temperature and the virus spread (Shahzad et al 2020b), while some research revealed that temperature led to a decrease in the virus infection rate (Iqbal et al 2020). However, in some investigation, different provinces had different effects; for instance, in the Hubei province, temperature effect is positive, while Jiangsu showed a negative effect (Shahzad et al 2020a).…”
Section: Literature Reviewmentioning
confidence: 98%